Peran Ekonomi Islam dalam Mendukung Pencapaian Sustainable Development Goals (SDGs) - Wulandari, Wulandari; Aulia Mutiara Salma (Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract The Sustainable Development Goals (SDGs) are a global development agenda aimed at achieving sustainable human well-being through a balance of economic, social, and environmental dimensions. However, achieving SDG targets in various countries still faces structural challenges, including poverty, social inequality, and environmental degradation. This study aims to analyze the role of Islamic economics in supporting the achievement of the SDGs by emphasizing the conceptual suitability and contribution of Islamic economic instruments to sustainable development. This study uses a qualitative approach with a systematic literature review method that discusses Islamic economics, maqāṣid al-sharī‘ah, Islamic social finance, and the SDGs. The results of the study indicate a strong convergence between Islamic economic principles and the goals of the SDGs, particularly in the aspects of social justice, inclusiveness, and sustainability. Maqāṣid al-sharī‘ah serves as a normative foundation that expands the meaning of sustainable development beyond economic growth to social welfare and environmental protection. Furthermore, Islamic economic and financial instruments such as zakat, waqf, Islamic microfinance, and green sukuk have strategic potential in supporting poverty alleviation, inequality reduction, and financing sustainable development. However, optimizing the role of Islamic economics still faces challenges such as low Islamic financial literacy, suboptimal institutional governance, and limited policy integration. Therefore, strengthening the synergy of policies, institutions, and innovation is necessary so that Islamic economics can contribute more effectively to achieving the SDGs. Keywords : Islamic economics, Sustainable Development Goals (SDGs), maqāṣid al-sharī‘ah, Islamic social finance, sustainable development.